Comprehensive surgery of complex scalp arteriovenous fistula: a successful trial - Ma, Zhiming; Zou, Zhihao; Xie, Dajiang; Qian, Linlin (Frontiers in Surgery, 2025)
BackgroundTraumatic scalp arteriovenous fistula is a rare vascular abnormality. Open surgical removal and embolization have been employed to address this condition.MethodsIn this report, we present a case involving a 41-year-old man who exhibited a progressively enlarging pulsatile mass in his right occipital scalp. Computerized tomography angiography (CTA) and digital subtraction angiography (DSA) identified a complex scalp arteriovenous fistula (S-AVF). The combination of clinical symptoms and neuroimaging findings facilitated the diagnosis.ResultsFollowing a thorough discussion, we implemented a comprehensive strategy that included both endovascular embolization and surgical resection. The patient demonstrated an excellent prognosis with no reported discomfort.ConclusionsA comprehensive surgical approach should be considered in the management of patients with complex scalp arteriovenous fistula.